Structural state awareness through integration of global dynamic and local material behavior. (May 2019) - Habtour, Ed M; Cole, Daniel P; Kube, Christopher M; Henry, Todd C; Haynes, Robert A; Gardea, Frank; Sano, Tomoko; Tinga, Tiedo
Structural health monitoring and nondestructive inspection techniques typically assess the lifecycle and reliability of high-value aerospace, mechanical, and civil systems. Maintenance and inspection intervals are typically time-based and dependent on the structural health monitoring/nondestructive inspection technique to detect macroscale damage resulting from fatigue or environmental damage. The current work proposes an integrated materials-structures-dynamics approach for providing state awareness of structural health. The proposed approach shifts the conventional structural health monitoring/nondestructive inspection focus of searching for cracks to a health state awareness based on tracking changes in the energetics of the materials-structures-dynamics states. Energy variations are tracked in a cantilevered structure exposed to nonlinear harmonic oscillation, where the strain energy of the beam was derived and used to determine a health state index. Nanoindentation was used to probe the near-surface mechanical properties of the beam to characterize local material variations as a function of fatigue cycles. A nonlinear ultrasonic approach was considered in order to connect the local material behavior changes to the variations in the dynamic performance of the beam. The intent of the investigation was to connect the traditionally detached materials, structural, and dynamics approaches to structural health monitoring/nondestructive inspection, while providing a framework for enabling damage precursor detection.